Research on the Web-based On-line Monitoring Technology of the Smart Substation Primary Equipments - Xinbo Huang; Chen Tao; Shuliang Ji; Haitao Zhu; Zhouxiong Zhang; Xiaokuan Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Smart substation primary equipment on-line monitoring technology is an important part of the realization of substation intelligentizes monitoring. In order to meet the requirements of smart substation on high-speed, efficient, steady on-line monitoring system, the sharing of online monitoring data of the power station and to improve interoperability of on-line monitoring device, the primary equipment on-line monitoring technology of smart substation based on the network is proposed by this paper. Based on the analysis of the substation primary equipment monitoring parameters, according to the three levels and two network structure, the author designed primary equipment monitoring terminal (process level), primary equipment on-line monitoring IED (bay level), the monitoring center (station level)respectively, and between each level there are communication network structures. The scene practical operation analysis shows that, on-line monitoring system for substation which based on the network is stable and reliable, and the change of the equipment running status can be monitored accurately and timely.